The Role Of The Green Economy, Technological Innovation, Stock Market Advantages In Sustainable Development - Nurmala Galuh Pramesthi; Sevira Pahlevi Santoso; Hwihanus (International Journal of Educational Evaluation and Policy Analysis, 2024)
A green economy to achieve sustainable development provides technological innovation and stock market profits in a sustainable social and environmental economy. To accelerate the transition to an environmentally friendly economy, companies need to understand the impact of implementing environmentally friendly policies and activities on the economy. Results show that green economic growth policies produce future aggregate stock market returns are lower, consistent with the perceived reduction in risk argument by investors. As this research increases our understanding of how the transition to a more sustainable green economy can impact the aggregate profitability of financial markets, implementing a green economy is important to implement appropriate measures to support it sensitively without incurring large costs that adversely impact the health of the economy. Increasing the driving force of technological innovation is the need to comply with environmentally friendly transformation in the economy and realize high-quality economic growth in technological innovation that does not provide support for green economic growth, but over time the impact of technological innovation on economic growth will change to positive. This shows that increasing the ability of technological innovation to encourage environmentally friendly economic efficiency.